EFRT: A realistic model of human exercise, fatigue and recovery - Finke, A.; Drake, J.; Ferguson, R. (Journal of Science and Cycling, 2023)
We discuss mathematical models for endurance exercise. Such models are needed to accurately assess athletes' fitness (e.g. for guiding training or identifying talent); and to predict performances (e.g. for optimising race strategies and pacing in track-cycling events).